Distinct drivers of stadium attendance and online streaming: evidence from the Chinese women's super league - Liu, Tiantian; Li, Shanshan; Han, Zhiyu; Niu, Huayong (Frontiers in Sports and Active Living, 2025)
IntroductionThis study investigates the determinants of women's football viewership by comparing stadium attendance and online streaming demand in the Chinese Women's Super League during the 2023 season.MethodsMatch-level data were analyzed using ordinary least squares regression for 125 games with attendance records and negative binomial regression for 126 games with streaming data.ResultsThe results revealed distinct drivers across the two forms of consumption. Higher stadium attendance was associated with the home team's historical championships, lower per capita disposable income in the host city, and weekend scheduling. In contrast, online streaming demand was shaped by competitive balance and team quality, as well as seasonal variation and the length of time replay videos remained accessible.DiscussionThese findings demonstrate that live attendance is influenced primarily by structural and contextual factors, whereas digital audiences respond more directly to match competitiveness and content availability. The study highlights the complementary nature of in-person and digital engagement in women's football and underscores the growing role of data-driven approaches in advancing audience research. By integrating audience behavior analysis with innovations in digital technology, wearable monitoring, and artificial intelligence, this research contributes to the development of interdisciplinary frameworks that can enhance fan engagement, expand the visibility of women's football, and support broader applications of sports science in the digital era.